2013
DOI: 10.1093/nar/gkt274
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the nature of reading frame transitions observed in prokaryotic genomes

Abstract: Our goal was to identify evolutionary conserved frame transitions in protein coding regions and to uncover an underlying functional role of these structural aberrations. We used the ab initio frameshift prediction program, GeneTack, to detect reading frame transitions in 206 991 genes (fs-genes) from 1106 complete prokaryotic genomes. We grouped 102 731 fs-genes into 19 430 clusters based on sequence similarity between protein products (fs-proteins) as well as conservation of predicted position of the frameshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 86 publications
1
44
0
1
Order By: Relevance
“…On two elements, msi172 and msi171 were found as a single ORF; moreover, they exist as a single ORF on the Tn4371 family of ICEs that lack QseM homologs (Table S1) (10,12). This combination of sequence features is common to PRF sites (13) and suggested that a PRF site might exist in the msi172 mRNA that could promote the fusion of the Msi172 coding sequence with that of Msi171 during translation. PRF events involve a slippage of the ribosome with respect to the mRNA during translation, resulting in a +1 or −1 shift in the reading frame.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…On two elements, msi172 and msi171 were found as a single ORF; moreover, they exist as a single ORF on the Tn4371 family of ICEs that lack QseM homologs (Table S1) (10,12). This combination of sequence features is common to PRF sites (13) and suggested that a PRF site might exist in the msi172 mRNA that could promote the fusion of the Msi172 coding sequence with that of Msi171 during translation. PRF events involve a slippage of the ribosome with respect to the mRNA during translation, resulting in a +1 or −1 shift in the reading frame.…”
Section: Resultsmentioning
confidence: 96%
“…The employment of a PRF as a mechanism to control the frequency of horizontal transfer has not, to our knowledge, been reported for ICEs or plasmids, but PRF sites are a feature of transposase production by several insertion sequences, where frameshifting is thought to prevent high-frequency transposition that would have a detrimental effect on host survival (28). Several common features of +1 PRF sites have been identified; however, it is clear that individual sites often have distinct features, which could obscure detection from sequence information alone (13,29,30). The msi172 PRF site discovered here differs from other characterized PRF sites and merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have used telomere maintenance to illustrate how defects in ribosome function can lead to altered gene expression, we anticipate that other pathways are also affected in yeast. Studies in bacteria have identified an unexpectedly large number and diversity of recoding events (32)(33)(34), suggesting that such recoding is pervasive in biology. Although we have demonstrated that ∼10% of mammalian mRNAs harbor strong candidate −1 PRF signals, our studies also show that this class of cis-acting mRNA elements evolves quickly and does not appear to be well conserved (30).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous mRNAs have evolved special sequence elements to alter the meaning of specific codons or to result in ribosomes shifting reading frame or even bypassing long untranslated regions 22 . Alterations in genetic decoding are expected to exist in almost all organisms, and bioinformatics screens of bacterial genomes are revealing thousands of genes the decoding of which requires ribosomal frameshifting [23][24][25] , and metagenome analyses of environmental samples point to many organisms with variant genetic codes 26 .…”
mentioning
confidence: 99%